THE ROLE OF UCLG ASPAC IN MANAGING WASTE IN DKI JAKARTA PROVINCE IN 2016 - 2019: OPPORTUNITIES & CHALLENGES: THE ROLE OF UCLG ASPAC IN MANAGING WASTE IN DKI JAKARTA PROVINCE IN 2016 - 2019: OPPORTUNITIES & CHALLENGES - Septi Annissa Rahmania; R. Dudy Heryadi; Laode Muhammad Fathun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
Abstract: Waste has become a global issue that worries the world because of increasing waste production due to increasing population and higher living standards. Areas that have activities and densely populated certainly cannot avoid this disaster, even it makes difficult for local governments to solve this problem. UCLG ASPAC in this case acts as an international organization whose aim to realize sustainable development in the urban areas of Asia Pacific countries that can help to deal with waste. This study uses the theory of the role of inter-governmental organizations (IGO) according to Clive J. Archer. The results of this research analysis of the role of UCLG ASPAC can be assumed to be instruments, arenas, and independent actors in handling waste in Jakarta. And can strengthen aspects of regulative, normative, cognitive culture together with the Pemprov DKI Jakarta to work together to solve the waste problem that has not been completed. Keywords: role, international government organization, local governments, waste management,